Minimum Error Design for Transceiver Models Using Software-Defined-Radio and GNU Radio - Ridwan, Muhammad Kamil; Hakim, Nurul Fahmi Arief; Kustiawan, Iwan; Fatimah, Desi; Ridwan, Azwar Mudzakkir (International Conference on Wireless and Telematics (Online), 2024)
Software Defined Radio (SDR) refers to a radio system in which software defines a subset or the entirety of its components. SDR technology offers numerous benefits, such as its adaptable nature and the capability to offer more cost-effective radio systems through the substitution of hardware functions with software configurations. In light of the numerous benefits associated with SDR technology, considerable ongoing research is devoted to this subject matter. Nevertheless, a significant research deficit persists in the advancement of SDR technology with respect to the errors that are present in the SDR model design process. The purpose of this article is to examine how SDR transceivers are designed and simulated utilizing the GNU Radio software. The simulation consists of three schemes, the first of which conducts 2870 trials and the second and third of which employ ADALM-PLUTO as the transceiver. The outcomes derived from this investigation provide empirical evidence that the transceiver configuration utilizing SDR and GNU Radio is capable of executing 16-QAM modulation. By utilizing the block diagram integrated within GNU Radio, one can achieve improved reception quality with reduced noise levels. Moreover, the adaptability of SDR facilitates the configuration of transceivers and allows for their utilization as required.